FAMILIARIZATION WITH THE HYGIENIC ASSESSMENT OF THE CONDITION OF THE ORAL MUCOSA IN ORTHOPEDIC TREATMENT - Ravshanov Isroil Ravshanovich; Khotamova Madinakhon Anvarovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. The most common causes of complications in the mouth and the unsuitability of fixed structures are considered to be inflammatory processes, caries and its complications (16,4–25,2 %) [7,8,12], thermal burns of the pulp (4.3%) [4,6,9], cementation of the supporting crowns (8-21% of all complications). These processes often develop in the area of the edge of artificial crowns and are caused by the destruction of the cement layer that fixes the non-removable prosthesis. One of the typical complications of dental prosthetics, which often develops within the first year after fixation of the artificial crown, is the exposure of the neck of the tooth root due to gum recession [3,5,11].